Civil engineering design project technical report / Abdullah Farhan Rahman - Rahman, Abdullah Farhan (2023)
A popular and very dependable structural analysis and design program is called PROKON. For civil engineers who desire to be proficient in structural analysis and provide the requested designs, this tool is both simple to learn and use. Engineers may now build more intricate and expansive structural constructions thanks to structural analysis tools. For instance, it is now possible to imitate the behavior of larger structures like multi-story buildings in an accessible setting.Time is saved because to this app.It solves complicated issues quickly while making them appear to be fairly easy.Finding out the outcomes of several calculations does not take much time. The structure analysis tool is particularly adaptable since it readily comprehends the physical architecture and its many aspects.